Application of Modified Ventilator Bundle and Its Effect on Weaning and Ventilation Days among Critical Ill Patients - Amany S. Eweas; Sahar Y. Mohammad; Jehan S. A. Sayyed; Marwa M. Abd Elbaky; Magda M. Bayoumi (Evidence-Based Nursing Research)
Context: Modified ventilator bundle is the group of interventions supported by evidence to prevent ventilator-associated pneumonia and other related complications that commonly occurred in mechanically ventilated patients. Furthermore, it helps in reducing the mortality rates and hospital length of stay.